Review of social media potential on knowledge sharing and collaboration in tourism industry - Nezakati, Hossein *; Asra, Amidi; Yusmadi, Yah Jusoh; Shayesteh, Moghadas; Yuhanis, Abdul Aziz; Roghayeh, Sohrabinezhadtalemi (Elsevier, 2015)
Social media have revolutionized communication in tourism industry. Review of the current literature revealed that previous studies have examined the role of information technology in tourism, but still there is a lack of study to reveal how social media promote knowledge sharing processes. To this end, the authors review extant related articles in knowledge management in tourism. The purpose of this study is understanding of knowledge sharing in social media in tourism sector. Specific concentration is on integration of tacit knowledge sharing during pre-travelling decision making. Finding of this study contribute to researchers, organizations and policy makers in tourism industry.